1987
DOI: 10.1073/pnas.84.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression and replication of hepatitis B virus genome in an integrated state in a human hepatoma cell line transfected with the cloned viral DNA.

Abstract: A human hepatocellular carcinoma cell line (Huh6-c15) was transfected with a recombinant DNA molecule that consists of tandemly arranged hepatitis B virus (HBV) genome and a neomycin-resistant gene. One done resistant to G-418 produces and releases surface antigen and e antigen into medium at a high level and accumulates core particles intracellularly. This clone has a chromosomally integrated set of the original recombinant DNA and produces a 3.5-kilobase transcript corresponding to the pregenome RNA as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
120
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 28 publications
5
120
0
Order By: Relevance
“…5 Within the last decade, several HBV expressing cell lines have been established by transfecting viral DNA into liverderived human cell lines and by selecting novel cell lines containing stably integrated HBV genomes. [6][7][8] The most widely used are the HepG2 2.2.15 cell line (2.2.15) derived from the HepG2 hepatoblastoma cell line and HB611 derived from the HuH6 hepatoma cell line. These and other cell lines have led to considerable progress in the study of HBV in vitro.…”
mentioning
confidence: 99%
“…5 Within the last decade, several HBV expressing cell lines have been established by transfecting viral DNA into liverderived human cell lines and by selecting novel cell lines containing stably integrated HBV genomes. [6][7][8] The most widely used are the HepG2 2.2.15 cell line (2.2.15) derived from the HepG2 hepatoblastoma cell line and HB611 derived from the HuH6 hepatoma cell line. These and other cell lines have led to considerable progress in the study of HBV in vitro.…”
mentioning
confidence: 99%
“…By the time the studies described above were completed, most work on hepadnavirus replication was shifting away from animal models to transfection-based studies using liver tumor cell lines (Tsurimoto et al 1987;Yaginuma et al 1987;Condreay et al 1990). Further work with animal models focused primarily on understanding the host response to infection and development of antiviral therapies.…”
Section: The Hepadnavirus Life Cyclementioning
confidence: 99%
“…It was not until 1986 that the HepG2 line of human liver tumor cells (Aden et al 1979) was found to support HBV replication from cloned viral DNA (Sureau et al 1986;Sells et al 1987). In the following 3 years, two other human liver tumor lines, Huh6 and Huh7, and a rat hepatoma cell line were also shown to fulfill this need (Tsurimoto et al 1987;Yaginuma et al 1987;Shih et al 1989). As discussed below, by this time many key steps in hepadnavirus replication had been revealed through the use of animal models and primary hepatocyte cultures.…”
mentioning
confidence: 99%
“…However, the differentiated state of the hepatocytes in these cultures can be maintained only for a limited amount of time. Propagation of HBV in cell culture has been achieved by transfection of closed circular HBV DNA in human hepatoma cell lines (HepG2 or HUH7) (Sureau et al, 1986;Sells et al, 1987;Tsurimoto et al, 1987). However, the latter system did not mimic the in vivo process of viral infection, including virus penetration and early biochemical events.…”
Section: Introductionmentioning
confidence: 99%